(untitled) (The Pakistan Development Review, 2002)
This paper challenges the popular view that devaluation of the rupee is inflationary. Recent developments in the theoretical literature are reviewed to explain why consumer prices would be unresponsive to exchange rate changes in the short run. Then empirical tests are conducted for Pakistan during the period 1982 to 2001 to examine whether inflation is systematically related to changes in the exchange rate. The empirical analysis finds no association between rupee devaluations and inflation in Pakistan. It appears, therefore, that concerns about the inflationary consequences of rupee devaluation are unsupported by the facts.